Stability analysis of photovoltaic system under grid faults - Nivedita Pati; Babita Panda; Bhagabat Panda (Institute of Advanced Engineering and Science, 2020)
This work includes the establishment of a Photovoltaic system connected to the grid by means of an inverter. The fundamental goal of the work is to incorporate an advanced active power flow management scheme in order to adopt load at any weather condition along with the advantage of maximum active power flow and zero harmonics from PV inverter to the grid. The outcome of analysis and control design of grid connected PV inverter using a Proportional-Integral (PI) control technique is based on synchronous dq rotating reference frame so as to achieve maximum output voltage and record the active power. It has been observed that the model provides a better rate of stability as compared to the existing topology.